Choroidal macrovessels: multimodal imaging findings and review of the literature. Issue 4 (4th January 2021) - Gallo, Beatrice; de Silva, Samantha R; Mahroo, Omar A; Saihan, Zubin; Patel, Praveen J; Dowler, Jonathan G; Pavesio, Carlos; Keane, Pearse A; Tufail, Adnan; Sagoo, Mandeep S
Abstract : Background/aims: To describe clinical and multimodal imaging features in a cohort of choroidal macrovessels. Methods: Demographics and multimodal imaging features of 16 eyes of 13 patients with choroidal macrovessels were reviewed. The multimodal imaging included colour fundus photography, fundus autofluorescence (FAF), spectral domain enhanced depth imaging optical coherence tomography (OCT), en face OCT, OCT-angiography (OCT-A), B-scan ultrasonography (US), fluorescein angiography (FFA) and indocyanine green angiography (ICGA). Results: Three patients had bilateral involvement. On colour fundus photography, three patterns were evident (a clearly visible orange-red vessel; a track of pigmentary changes; spots of mild pigmentary changes). Vessel orientation was horizontal (11 eyes), oblique (4 eyes) or vertical (1 eye). In 2 eyes, the vessel was extra-macular. OCT in all cases showed a hyporeflective choroidal area with posterior shadowing and elevation of the overlying retina. Subretinal fluid was present in 4 eyes. FAF (12 eyes) was normal (7 eyes) or showed a hypofluorescent/hyperfluorescent track (4 eyes) or linear hyperautofluorescence (1 eye). En-face OCT (2 eyes) revealed the course of the macrovessel at the level of choroid and choriocapillaris. On OCT-A (2 eyes) the vessel had a reflectivity similar to surrounding vessels but larger diameter. B-scan US (8 eyes) showed a nodular hypoechogenic lesion. FFA (5 eyes) showed early focal hyperfluorescence (4 eyes) not increasing in later phases, or was normal (1 eye). ICGA (6 eyes) showed early hyperfluorescence of the vessel. Conclusions: Choroidal macrovessels can mimic other entities, leading to underdiagnosis. Appreciating relevant features on different imaging modalities will aid a correct diagnosis.